Collaborative research efforts and related activities of the Office of Rare Diseases Research at the USA National Institutes of Health (Italian Journal of Public Health, 2009)
Introduction: Rare diseases present unique challenges to meet the numerous and varied needs of the rarediseases community and it is required to identify and address these needs. Significant financial andpersonnel resources are required to address these needs identified. The Office of Rare Diseases Research(ORDR) at the USA National Institutes of Health (NIH) has attempted to meet many of these needs incollaborative efforts with the research Institutes and Centers of NIH and other partners in the private andpublic sectors in the USA and around the world. Several of the activities of the NIH and the ORDR arepresented as possible collaborative efforts available to research investigators and include the Rare DiseasesClinical Research Network, the Bench-to-Bedside research program at NIH, the Genetic and Rare DiseasesInformation center, the genetic test development program, and the information on clinical research studiesmade available through Clinical trials.gov. The value of an appropriate family medical history is discussed asare the provisions of the Genetic Information Non-Discrimination Act of 2008 (GINA). Definitions of rare ororphan diseases vary from country to country and may cause some confusion to the rare diseases community.Conclusions: Rare diseases are not limited by geographical or historical boundaries and global partnershipsof the rare diseases community are experiencing rapid expansion to assist in the development of orphanproducts for the prevention, diagnosis and treatment of rare diseases and conditions. The unmet needs of therare diseases community require additional innovative research and educational programs to reach theextensive global populations affected by the thousands of different rare diseases including activities with theNational Organization for Rare Disorders and the Genetic Alliance.
Keywords: rare diseases; orphan diseases; research collaboration; orphan drugs; orphan products; Office of Rare Diseases Research